The first species of Scydmoraphes (Coleoptera, Staphylinidae, Scydmaeninae) in China - Jałoszyński, Paweł (Zootaxa, 2019)
Scydmoraphes Reitter, 1891 is a Palaearctic genus with 120 species (Schülke & Smetana 2015; Jałoszyński 2015a); its morphological structures were illustrated by Jałoszyński (2015b, c). Distribution of over 90 species is restricted to one country in the western part of the region, the remaining species occur in a few countries each, also mainly in the western Palaearctic. Only three species have a broader distribution within Europe, each in about 20 countries. In Asia, most species are restricted to its western areas (mainly Turkey), with only two species recorded from South Asia (northern Pakistan), one broadly distributed Eurasian species (S. minutus Chaudoir, 1845) found in the Russian Far East, and one species inhabiting the Japanese mainland (Jałoszyński 2004; Schülke & Smetana 2015). The first member of Scydmoraphes is here recorded from China.